Improving the Literacy Ability of Children Aged 5-6 Years Through Letter Flow Maze Media - Sumarni, Sri; Pagarwati, Lia Ayu; Fadhilah, Adela Nurul; Pasaribu, Roma Satika Pasaribu; Aulia, Renata Putri; Qonita, Novi Arini; Mastiur Hutagalung, Lisdan Agave (UNIB Press, 2025)
Literacy skills are an important aspect in the development of early childhood literacy. At the age of 5-6 years, children begin to be introduced to letters as a basis for learning to read and write. Using the letter flow maze media, this study attempts to improve the ability of vowel literacy in children aged 5-6 years at Al-Kautsar Indralaya Kindergarten. This study was conducted using the Classroom Action Research (CAR) approach involving 10 children as participants. Data were obtained through observation and interview activities, then analyzed qualitatively with descriptive methods. The results of the study showed that before the action (pre-action), only 40% of children were able to recognize vowels as expected. After the application of the letter flow maze media in Cycle 1, the percentage increased to 60%. Further improvement occurred in Cycle 2, where 90% of children had shown the ability to recognize vowels with the Very Well Developed (BSB) category. These results prove that the use of letter flow maze media is effective in improving vowel literacy in early childhood at Al-Kautsar Indralaya Kindergarten.